Vitvitska N.M. The role of authentic materials in the implementation of CLIL and ESP approaches in the preparation of future English language teaching professionals - (:unkn) unknown (Українсько-польське наукове видавництво «Liha-Pres», 2025)
Contemporary transformations in higher pedagogical education necessitate updating methodological approaches to educating future English teachers. In the context of European integration and the implementation of a competence-based model of education, integrative approaches that combine language and professional training, in particular CLIL (Content and Language Integrated Learning) and ESP (English for Specific Purposes), are becoming particularly relevant. An important component of the implementation of these approaches is the use of authentic materials that bring the learning process closer to the real conditions of academic and professional communication, contributing to the formation of communicative competence in future specialists.